Babukong Ritual and the Persistence of Dayak Ma'ap Cultural Identity in the Modern Era - Tindarika, Regaria (Universitas Tanjungpura, 2026)
This study examines the transformation, functions, and meanings of the Katipak Dance within the Babukong funeral ritual of the Dayak Ma’ap community in the context of modernization and cultural globalization. The urgency of this research lies in the increasing pressure of global culture, which threatens the continuity of local traditions and weakens cultural identity. This study aims to (1) describe the role of the Katipak Dance in the structure of the Babukong ritual, (2) analyze its social, cultural, and spiritual functions, and (3) identify the forms of transformation and community strategies in preserving the tradition. This research employs a qualitative method with an ethnographic approach. Data were collected over a period of three months through participant observation, in-depth interviews with three key informants; Sakon (81 years old, customary leader and ritual authority), Agustinus Alat (76 years old, dancer and ritual practitioner), and Dimoarto (61 years old, Babukong cultural practitioner) and documentation. The findings show that the Katipak Dance remains a central element of spiritual communication, social cohesion, and cultural transmission within the Babukong ritual. However, modernization has influenced changes in its performance, duration, and modes of transmission. The Dayak Ma’ap community responds to these changes through adaptive strategies such as ritual revitalization, youth involvement, and contextual adjustments without eliminating core cultural values. This study highlights the importance of Babukong as a cultural mechanism that sustains identity, strengthens social solidarity, and ensures the continuity of local wisdom in the modern era.